Pendampingan Perancangan SOLO Taxonomy Berbasis Tri Pramana dalam Praktik Pembelajaran dan Penilaian Formatif SDN 24 Dauh Puri : Pengabdian - Dewa Made Dwicky Putra Nugraha; I Wayan Aryawan; I Made Astra Winaya; Ni Nyoman Sri Mastini; I Wayan Gede Anggra Wisana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This mentorship program addressed gaps in classroom design and formative assessment at SDN 24 Dauh Puri notably, limited capacity to assess depth of student understanding and insufficient application of deep-learning strategies. This program combined in-service and on-service model to integrate theoretical grounding with classroom practice. Activities comprised an introductory session on SOLO Taxonomy and Tri Pramana, collaborative lesson-plan workshops, followed by structured independent classroom trials by 16 teachers,, and an online reflection and evaluation meeting. Evaluation drew on lesson-plan artifacts, teachers’ implementation reports, formative assessment observations, and synthesized teacher testimonials. Results indicate full conceptual uptake among participants (mean understanding 100%), successful production of SOLO-aligned Lesson Plans, and at least two implementations per teacher. Observable impacts included more systematic student reasoning (movement toward relational and extended-abstract levels), enhanced reflective classroom interactions via the Tri Pramana cycle, and improved formative assessment precision through SOLO-based rubrics. The study recommends creating a rubric/item bank, extending practical implementation time, and establishing follow-up collaborative forums to sustain and scale the instructional innovation.